INTENSIVE CARE MATERNAL IN PERU. MANAGEMENT OF HYPERTENSIVE DISORDERS PREGNANCY - Jara Mori, Teófilo (2015)
National experience on obstetrical intensive care in various Health Ministry hospitals is little and dispersed, mainly due to low patients volume with this type of pathology. The seriously sick pregnant patient constitutes a challenge for the intensivist physician due to the special maternal status in regards to physiological requeriments and laboratory levels, to critical pregnancy own or coincident pregnancy diseases and to the presence of a fetus with physiological peculiarities and diverse risks, such as the pharmacologic one. In our experience, from 1997 through 2006, main admission indications to the Maternal Perinatal National Institute Intensive Care Unit have been hypertensive diseases of pregnancy (47,5%), sepsis – septic shock, severe hemorrage – hemorragic shock, among others, and these are the main maternal death causes.